THE EFFECT OF APPLICATION OF THE ACTIVE DEBATE METHOD ON THE SPEAKING SKILL OF STUDENTS IN CLASS V INDONESIAN LANGUAGE LEARNING CONTENT AT SD NEGERI BORONGKANANG, DISTRICT BONTONOMPO, REGENCY OF GOWA - Ameliah, Nur Azizah; Patta, Rahmawati; Atjo, Syamsuryani Eka Putri (International Journal of Elementary School Teacher, 2023)
This research was conducted based on the problem of students' speaking skills. The purpose of this research is to find out the description of the application of the active debate method, to know the description of students' speaking skills, and to determine the effect of the application of the active debate method on the speaking skills of fifth grade students at SD Negeri Borongkanang Kec. Bontonompo, Gowa Regency. This research is included in experimental research with a quantitative approach. The design used in this study was a quasi-experiment with a nonequivalent control group design. The population in this study were all fifth grade students at SD Negeri Borongkanang, Bontonompo District, Gowa Regency. The samples in this study were 16 students in class VA and 16 students in class VB who were selected using simple random sampling technique. The data in this study were collected using observation sheets and assessment instruments. Data were analyzed using descriptive and inferential analysis. The results of the descriptive analysis show that the application of the active debate method goes very well. The results of the inferential analysis using the independent sample t-test showed that there were differences in the results of the post-nontest questionnaire between the experimental class and the control class, which meant that the increase in students' speaking skills in the experimental group was better than the control group. So it can be concluded that: (1) the learning process by applying the active debate method is very effective; (2) the results of student assessments show an increase in students' speaking skills in learning; (3) there is an effect of the application of the active debate method on the speaking skills of fifth grade students at SD Negeri Borongkanang, Bontonompo District, Gowa Regency.